FOSTERING DISCIPLINE THROUGH DRUM BAND EXTRACURRICULAR ACTIVITIES IN CHILDREN AGED 5-6 YEARS - Candra, Putri Ameilia; Akhtim Wahyuni (Antis Publisher, 2024)
Objective: The study aims to instill a disciplined attitude in children aged 5–6 years through drum band extracurricular activities at RA Muslimat NU 10 Banin Banat, Gresik. Methods: This research adopts a descriptive-qualitative method. Data collection was conducted through observation, interviews with the principal, drum corps coach, class teachers, and participating children, as well as documentation. Results: The findings reveal that the drum band extracurricular effectively fosters discipline through consistent signaling by the instructors, such as long whistles and three short whistles, each conveying specific instructions. Non-compliance is addressed through direct reprimands. The discipline cultivated during these activities extends to daily school routines, where children consistently place their shoes on racks, line up when entering the classroom or during recess, and maintain order when leaving school. Novelty: This research highlights the unique contribution of drum band extracurricular activities in developing discipline among young children. It demonstrates how structured and consistent techniques, such as whistle commands, can effectively influence children’s behaviors both during extracurricular sessions and in their broader daily routines, offering valuable insights for early childhood education practices.